Impact of Financial Literacy, FinTech, and Managerial Ability on Financial Performance of Beverage MSME in Sukabumi - Agustiani, Rayhani; Norisanti, Nor; Komariah, Kokom (International Journal Administration, Business & Organization, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role as the backbone of the national economy. However, despite their vital role, many MSME actors consistently face significant challenges, especially in financial and operational management. This is clearly evident from the tendency of their income to be uneven (volatility) and the low level of financial stability among the operators. This situation is the main driver of the research, which aims specifically to identify key factors that can effectively improve their financial performance. Thus, using purposive sampling techniques, this quantitative study with an associative approach seeks to examine the impact of managerial expertise, financial literacy, and financial technology on the financial performance of beverage MSMEs in Sukabumi City. The study includes 86 respondents. The primary findings show that financial performance is positively and significantly impacted by both managerial skill and financial literacy. Financial technology, on the other hand, was found to have no discernible impact. These results suggest that improving MSME actors' managerial skills and financial literacy should be the primary goal in order to achieve stability and long-term improvements in financial performance.